2021
DOI: 10.1002/ppul.25367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID‐19 lockdown on sleep duration in children and adolescents: A survey across different continents

Abstract: Background A parent survey was conducted to assess the sleep habits of children residing in various countries before and during the SARS‐CoV‐2 pandemic. It was hypothesized that lockdown would be associated with increased sleep duration. Methods Outcomes were changes in bedtime, wake time, and sleep duration in the pandemic compared to before. Logistic regression was applied to evaluate the effects of age and covariates on outcomes. Results A total of 845 questionnaires completed from May 1 to June 10, 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 24 publications
10
54
2
Order By: Relevance
“…This can be attributed to the nationwide lockdown resulting in complete restriction of movement and a temporary substitution of classroom teaching to the virtual platform. The duration and parameter-based findings revealed the shift in bedtime and waking time in majority of the participants, which was similar to the findings published by Kaditis et al, that noted a similar change in the sleep and wake time of the participants [10]. The sudden shift of in-house learning to the virtual mode caused students to spend a lot of time in front of electronic gadgets which indefinitely tends to affect sleep health and hygiene.…”
Section: Discussionsupporting
confidence: 86%
“…This can be attributed to the nationwide lockdown resulting in complete restriction of movement and a temporary substitution of classroom teaching to the virtual platform. The duration and parameter-based findings revealed the shift in bedtime and waking time in majority of the participants, which was similar to the findings published by Kaditis et al, that noted a similar change in the sleep and wake time of the participants [10]. The sudden shift of in-house learning to the virtual mode caused students to spend a lot of time in front of electronic gadgets which indefinitely tends to affect sleep health and hygiene.…”
Section: Discussionsupporting
confidence: 86%
“…They reported an increase in sleep duration but a higher proportion reported poor sleep quality during COVID-19 social distancing restrictions. Increased sleep duration during COVID-19 confinement has been consistently reported in adolescents (Kaditis et al, 2021;Ramos Socarras et al, 2021). However, long-distance runners have been reported to have inadequate sleep compared to recommendations (Garcia et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of insufficient sleep per night for weekdays reported in a study decreased from 16% during COVID-19 Stay-at-Home orders to 8% in college students [ 10 ]. A cross-sectional survey across different continents found that adolescents had fourfold increased odds for longer sleep duration on weekdays during the pandemic [ 19 ]. Another longitudinal study in the United States revealed that the percentage of sufficient sleep in school night increased to 64% during COVID-19 pamdemic from 57% before COVID-19 in adolescents, and this change was statistically non-significant.…”
Section: Discussionmentioning
confidence: 99%